Ticagrelor: a P2Y12 antagonist for use in acute coronary syndromes. Issue 3 (May 2012) - Wijeyeratne, Yanushi Dullewe; Joshi, Rashi; Heptinstall, Stan
Agents that inhibit platelet function are used routinely in the treatment and prevention of acute coronary syndromes. The main antiplatelet treatments used combine aspirin with one of the thienopyridine P2Y12 antagonists, either clopidogrel or prasugrel. By blocking the synthesis of thromboxane A2 in platelets and by blocking the effects of ADP, respectively, these agents reduce platelet activity, platelet aggregation and thrombus formation. Ticagrelor (marketed by AstraZeneca as Brilinta™ in the USA, and as Brilique ® or Possia ® in Europe) is a cyclopentyl-triazolo-pyrimidine, a new chemical class of P2Y12 antagonist that is now approved for use in the wide spectrum of acute coronary syndromes. In this article we provide an overview of ticagrelor. We discuss the differences in mode of action compared with other P2Y12 antagonists, examine its pharmacodynamic, pharmacokinetic and safety profile, and summarize the various clinical trials that have provided information on its efficacy in combination with aspirin. Ticagrelor appears to overcome some of the difficulties that have been encountered with other antiplatelet treatments, clopidogrel in particular.